Alasan Pembuktian Tindak Pidana Perzinahan Dengan Saksi Berjumlah 4 Orang Laki-Laki Dalam Hukum Pidana Islam - Adil Lubis, Muhammad Hafizh; Marpaung, Zaid Alfauza (JUSTICIA SAINS - Jurnal Ilmu Hukum, 2024)
The issue regarding the number of witnesses in criminal cases of adultery according to Islamic law is still a deep problem regarding why 4 men are required, so in this research the author will examine this in more depth. By using 3 problem formulations related to this research to find answers to the evidentiary reasons why the crime of adultery requires 4 male witnesses. This research is qualitative in nature with a normative juridical legal approach using two data sources, namely primary and secondary. The results of the research show that the concept of witnesses according to positive law only requires general criteria without distinction of gender, while the Islamic law of the majority of ulama requires witnesses to be male, with at least four people witnessing directly, and there is a difference of opinion with Ibn Hazm in interpreting), he stated that women's testimony can be accepted provided that women's testimony is considered half that of men's testimony